Back Cover: Solar RRL 1∕2017. Issue 1 (January 2017) - Meier, Sebastian; Maier, Stefan; Demberger, Carsten; Wolf, Andreas; Biro, Daniel; Glunz, Stefan W.
Abstract : Bifacial solar cells allow for an increased energy yield or a broadening of the energy output over the day, depending on the physical surrounding and module orientation. One bifacial cell structure of high interest is a passivated emitter rear totally diffused (PERT) cell using n‐type Czochralski‐grown silicon wafers, as represented on the foreground of the cover. There the front and the rear side of the bifacial n‐type PERT cell are shown which has been developed by Meier et al. (article no.1600005 ). A frequently used approach for the fabrication of this cell structure is the use of co‐diffusion, meaning the generation of the borondoped front emitter and the phosphorus‐doped back surface field in one single thermal process. Meier et al. describe a fast co‐diffusion process, realized in an industrial tube diffusion furnace as represented in the background of the cover.